Pengaruh Kualitas Pelayanan, Manfaat, dan Lokasi terhadap Keputusan Shahibul Mal memilih Asuransi Syariah di Indonesia - W., Irwan; Ashari, Nesha Rizky (Jurnal Ilmiah Ekonomi Islam, 2024)
The role of insurance has become crucial in securing the future. It is essential to know where to invest and what the benefits are. Therefore, the insurance system provides a riba-free environment where Shahibul mal invests their money and compensates for losses according to Sharia. This study aims to analyze the influence of service quality, benefits, and location on Shahibul mal's decision to choose Sharia insurance in Indonesia. The research is expected to provide deep insights into the impact of service quality, benefits, and location on Shahibul mal's decision in Indonesia. This study employs a quantitative method with data collection techniques through questionnaires (Google Forms) distributed via social media. The analysis method used is path analysis or Structural Equation Modeling (SEM). The findings of this research indicate that service quality, benefits, and location have a significantly positive influence on Shahibul mal's decision.